Concentrations of Pneumococcal IgA and IgM are compromised in some individuals with antibody deficiencies. Issue 5 (3rd September 2017) - Echeverría de Carlos, Ainara; Gómez de la Torre, Ricardo; García Carus, Enrique; Caminal Montero, Luis; Bernardino Díaz López, Jose; Suárez Casado, Hector; Molinos Matin, Luis; Tricas Aizpún, Lourdes; Harding, Stephen; Parker, Antony R.
ABSTRACT: The response to pneumococcal vaccination is assessed by measurement of antigen specific IgG only and is compromised in a number of antibody deficiencies. We measured the concentrations of Pneumococcal IgA and IgM in individuals with both normal and abnormal pneumococcal capsular polysaccharide (PCP) IgG concentrations. A higher number of individuals had abnormal pre-vaccination IgA and IgM concentrations below the lower limit of the normal range compared to the control group. Post vaccination a lower number of individuals had IgA and IgM concentrations below the upper limit of the normal range compared to the control group. Non responders had a higher percentage of individuals with a prior history of infection. In addition, individuals with a history of prior infection had lower pre- and post-vaccination concentrations of PCP IgG, IgA, and IgM. Post-vaccination IgA and IgM concentrations identified four groups of responses which correlated with prior history of infection. A higher percentage of individuals with abnormal PCP IgA and IgM concentrations had a history of prior infection compared to the percentage of individuals with normal concentrations. In individuals with an antibody deficiency, measurement of Pneumococcal IgA and IgM correlates with the number of individuals with prior history of infection.